2022
DOI: 10.1109/tnsre.2022.3144216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bimanual Cyclical Tasks From Single-Trial EEG-fNIRS Measurements

Abstract: Robot-assisted bimanual training is promising to improve motor function and cortical reorganization for hemiparetic stroke patients. Closing the rehabilitation training loop with neurofeedback can help refine training protocols in time for better engagements and outcomes. However, due to the low signal-to-noise ratio (SNR) and non-stationary properties of neural signals, reliable characterization of bimanual training-induced neural activities from single-trial measurement is challenging. In this study, ten hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…RAIN-COMPUTER interface (BCI) can provide a communication pathway between the brain and external devices [1,2]. To date, a large number of studies have demonstrated that kinematic parameters of hand movements are strong relative to non-invasive electroencephalogram (EEG) signals [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…RAIN-COMPUTER interface (BCI) can provide a communication pathway between the brain and external devices [1,2]. To date, a large number of studies have demonstrated that kinematic parameters of hand movements are strong relative to non-invasive electroencephalogram (EEG) signals [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research has found that frontal α rhythm asymmetry indicates approach/withdrawal tendencies related to emotions rather than the valence of emotions per se [53]. To examine these dynamics in more depth, our study considered the entire induction period, calculating average amplitude changes in Delta (1-4 Hz), Theta (4-8 Hz), Alpha (8-12 Hz), Beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and Gamma (30-80 Hz) rhythms for each channel under various emotional states. This approach is presented in Figure 15, which visually presents the differences between different emotions.…”
Section: Electroencephalography (Eeg) Data Analysismentioning
confidence: 99%
“…Third, compared to increasing movement types of unilateral limb, involving bilateral-limb movements to be discriminated from unilateral movements can improve multidimensional control and meanwhile maintain well decoding performance, which can be attributed to the distinct brain activation patterns of unilateral and bilateral movements [16]. In recent years, several studies have turned attention to the simultaneous bilateral movements' decoding from EEG signals, including bimanual center-out movements [17,18], bimanual reach-and-grasp movements [15], and bimanual cyclical tasks [19]. Actually, humans can perform tasks with two hands either simultaneously or sequentially.…”
Section: Neural Correlate and Movement Decoding Ofmentioning
confidence: 99%